2009
DOI: 10.1021/jm900473p
|View full text |Cite
|
Sign up to set email alerts
|

Improving Metabolic Stability by Glycosylation: Bifunctional Peptide Derivatives That Are Opioid Receptor Agonists and Neurokinin 1 Receptor Antagonists

Abstract: In order to obtain a metabolically more stable analgesic peptide derivative, O-β-glycosylated serine (Ser(Glc)) was introduced into TY027 (Tyr-D-Ala-Gly-Phe-Met-Pro-Leu-Trp-NH-3’,5’-Bzl(CF3)2) which was a previously reported bifunctional compound with delta/mu opioid agonist and neurokinin-1 receptor antagonist activities, and with a half life of 4.8 h in rat plasma. Incorporation of Ser(Glc) into various positions of TY027 gave analogues with variable bioactivities. Analogue 6 (Tyr-D-Ala-Gly-Phe-Nle-Pro-Leu-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 59 publications
2
54
0
2
Order By: Relevance
“…Some authors reported that the endogenous opioid system plays an important role in the regulation of feeding behavior (including food reinforcement) [8][9][10][11][12]. We proposed and substantiated a hypothesis on reciprocal interaction between the central and peripheral compartments of the endogenous opioid system [4] implying the involvement of the peripheral opioid system in the mechanisms of sensory satisfaction [2,6].…”
supporting
confidence: 67%
“…Some authors reported that the endogenous opioid system plays an important role in the regulation of feeding behavior (including food reinforcement) [8][9][10][11][12]. We proposed and substantiated a hypothesis on reciprocal interaction between the central and peripheral compartments of the endogenous opioid system [4] implying the involvement of the peripheral opioid system in the mechanisms of sensory satisfaction [2,6].…”
supporting
confidence: 67%
“…The structure and purity of compounds were confirmed by HPLC-MS analysis. The compounds, opi- T Ta ac ch hy yk ki in ni in n h hN NK K1 1 r re ec ce ep pt to or r b bi in nd di in ng g Neurokinin 1 receptor binding assays were performed as previously described [19]. Briefly, recombinant hNK1/CHO cells were grown to 90% confluence in a humidified atmosphere (95% air and 5% CO 2 ) at 37°C, in Ham's F12 medium supplemented with 10% foetal bovine serum, 100 U/mL of penicillin, 100 µg/mL of streptomycin and 500 µg/mL of Geneticin (G 418).…”
Section: Methodsmentioning
confidence: 99%
“…Such studies are particularly critical for newly developed therapeutics such as opioid analgesic peptides. In fact, many novel opioid peptides have been recently produced and have shown analgesic efficacy (Largent-Milnes et al, 2010; Yamamoto et al, 2009); however, molecular and trafficking mechanisms involved in their CNS delivery have yet to be identified. Discovery of mechanisms that determine brain permeation of these peptides will undoubtedly enable more efficient analgesia and an improved utility of these compounds as potential therapeutics.…”
Section: Resultsmentioning
confidence: 99%